Export of Continuing Education Programs: Skills and Technology (Case Study of Agricultural Universities) - Ilya A. Korshunov (National Research Mordova State University, 2019)
Introduction. Development of the economy via the introduction of new technologies stimulates the transfer of competencies through the expansion of exports of educational services in various professional sectors. The study of current skills and competences in the agricultural complex was carried out to identify the most competitive educational programs for adults’/continuing education on regional labor markets, which could be successfully exported by Russia to other countries. We also identified innovative educational products required by the agricultural sector in Russia. The purpose of this article is to study the process of implementation of adult/continuing education and training in Russian agricultural universities in international educational markets. Materials and Methods. Results of a questionnaire survey of higher education institutions under the Ministry of Agriculture of the Russian Federation concerning the implementation of short-term continuing educational programs exported to other countries were used here. Content analysis of popular skills was carried out to determine the most competitive strategies of exports to international educational markets (the case of Kazakhstan, Russia, and USA). The study was conducted on regional job search databases. The sampling scope involved above 3,000 current vacancies. Results. Theoretical and empirical results showed that countries purchase more complex skills if there is a demand for them in the country, and their own continuing education programs are not available. The acquisition of such skills is in demand in countries using a similar model of development of this industry. The increase in exports of Russian life-long education programs to international markets can be achieved by the transfer of high technologies in the agro-industrial sector. Potential countries for the export of continuing/ life-long education include those building cultural, political and socio-economical relationships with the Russian Federation. Discussion and Conclusion. This article is useful for heads of adult education departments of universities to determine the most perspective strategies for exporting continuing education services to international markets.